2016
DOI: 10.1155/2016/3746232
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of18F-FDG PET/CT and MRI in Assessing Pathological Complete Response to Neoadjuvant Chemotherapy in Patients with Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: Purpose. We performed this meta-analysis to determine the utilities of 18F-FDG PET/CT and MRI in assessing the pathological complete response (pCR) after neoadjuvant chemotherapy (NAC) in the same cohort of patients with breast cancer. Methods. Two reviewers systematically searched on PubMed, Scopus, and Springer (from the beginning of 1992 to Aug. 1, 2015) for the eligible articles. Heterogeneity, pooled sensitivity and specificity, positive likelihood ratio, negative likelihood ratio, and the summary receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 30 publications
6
32
0
2
Order By: Relevance
“…In the current study we focused on the use of PET/CT only and how to optimally use this to predict pCR total. Therefore, we cannot make a statement about the relative value of PET/CT compared to other imaging modalities, but this has been described by others [36, 37]. Nowadays, trastuzumab-labelled PET/CT scans are available with visualisation of HER2-positive lesions.…”
Section: Discussionmentioning
confidence: 97%
“…In the current study we focused on the use of PET/CT only and how to optimally use this to predict pCR total. Therefore, we cannot make a statement about the relative value of PET/CT compared to other imaging modalities, but this has been described by others [36, 37]. Nowadays, trastuzumab-labelled PET/CT scans are available with visualisation of HER2-positive lesions.…”
Section: Discussionmentioning
confidence: 97%
“…In a 2016 meta-analysis performed by Liu and colleagues, 58 data from 382 patients in six studies demonstrated sensitivity and specificity of 65% and 88% and 86% and 72% for MR imaging and PET, respectively, for pCR. Park and colleagues, 59 whose patient population was included in the analysis, also found that DWI had 100% sensitivity for pCR when a 55% increase in ADC was used at a cutoff.…”
Section: Mr Imaging and Pet In Localized Breast Examinationsmentioning
confidence: 99%
“…With numerous neoadjuvant therapy regimens available and many more treatments emerging, the identification of sensitive responders to NAC is highly significant. Numerous biomarkers (e.g., tumor size, node status, Ki‐67, HER2) and imaging‐based metrics (e.g., magnetic resonance imaging [MRI] and positron emission tomography) have been investigated for the prediction of pCR ; however, most efforts with traditional biomarkers measured prior to chemotherapy lack accuracy, and most efforts focusing on monitoring changes in morphological characteristics are indicative only of a late‐stage response . Therefore, a growing number of investigators have begun to focus on serum markers that may predict response to therapy.…”
Section: Introductionmentioning
confidence: 99%